Female Reproductive Age Mortality in in Kassala (Role of Malaria) - Mohammed, Abdalla Ali; Abdelfattah, Ahmed Ibrahiem; Elnour, Mahgoub Hassan (Gezira Journal of Health Sciences, 2018)
Objectives : To determine the mortality rates ,causes and contributing factors in women in reproductive age in Kassala Province. Setting: A refuge ,acute internally displaced people (IDP) camps, a town slums and an urban area, of total population of 214.100 in Kassala Province, East Sudan. Method: Community –based retrospective study ,using reproductive age mortality Survey (RAMOS) and verbal autopsy . Data was processed using SPSS for Windows Version11. Results: 121 deaths of female aged15-45 years, in four population sectors (refugees, IDP, slum dwellers & urban population) were identified. Slum dwellers show the highest reproductive age mortality rate 314/100,000women in reproductive age, while urban sector shows the lowest rate 199per 100,000WRA. Malaria is the major cause of death in three sectors with exception of IDP sector where pregnancy related causes contribute to 70% of death . Maternal mortality rate is highest in IDP population and slum dwellers(168&126 per100,000WRA)and lowest in urban population(47per 100,000WRA). Maternal mortality ratio is very high in slum dwellers, IDP and refugee population (1207,1192&914 per 100,000 live birth respectively),and 376 per100,000 live births in urban population. Malaria was found to be the major cause of indirect maternal deaths in all sectors.